Thanks from Angola - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Yona Lukanu Sebastiaõ, Coordinator of the Fraternidade Cristä do Desenvolvimento Comunitário (FCDC), writes to tell us of FCDC s agricultural support project, which helps the socially excluded to reintegrate in society. The project has a long...